2017
DOI: 10.18203/2320-6012.ijrms20173950
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic characSociodemographic characteristics and assessment of severity in organophosphorus poisoning in a tertiary care hospitalteristics and assessment of severity in Organophosphorous poisoning in a Tertiary care hospital

Abstract: Background: In Nepal pesticide poisoning is a common problem and organophosphorus poisoning (OP) is the most common form of acute poisoning responsible for majority of deaths. However, sufficient data is still lacking from Western region of Nepal. The present study analysed the sociodemographic factors of OP poisoning cases, the association of severity based on admission clinical score (POP scale) and lag time with mortality.Methods: This is a cross-sectional study conducted in patients of organophosphorus poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…On assessing the severity of the victims as per Peradeniya Organophosphorus Poisoning scale (POP scale), 38 (30.89%) patients had mild poisoning, 33 (26.83%) had moderate poisoning with 25 (20.33%) had severe poisoning in this study. Similar findings was seen in the study conducted by Timsinha S et al 26 This study shows that muscarinic effects (56.10%) predominates and appears first then nicotinic effects (29.27%). Study by Emerson et al, shows that muscarinic symptoms were found in 92% cases.…”
Section: Discussionsupporting
confidence: 91%
“…On assessing the severity of the victims as per Peradeniya Organophosphorus Poisoning scale (POP scale), 38 (30.89%) patients had mild poisoning, 33 (26.83%) had moderate poisoning with 25 (20.33%) had severe poisoning in this study. Similar findings was seen in the study conducted by Timsinha S et al 26 This study shows that muscarinic effects (56.10%) predominates and appears first then nicotinic effects (29.27%). Study by Emerson et al, shows that muscarinic symptoms were found in 92% cases.…”
Section: Discussionsupporting
confidence: 91%